Influence of glucomannan edible coating in guava quality during storage (Research, Society and Development, 2020)
Guava (Psidium guajava) is a highly perishable fruit and is considered as climacteric. Therefore, some alternatives are studied to prolong post-harvest conservation, one of them being the application of edible coatings, which are based on polysaccharides. The objective of this study was to evaluate the post-harvest conservation of uncoated (control – T0) guavas and with edible coating containing 0.5% (T0.5) and 1.0% (T1.0) of konjac glucomannan. The fruits were immersed in the solutions and stored under refrigeration at 4 ° C for analysis at 7 and 15 days of storage. The main parameters evaluated in relation to fruit quality during storage were firmness and color, and with the coating application it was possible to observe a maintenance of these parameters when compared to the control (p 0.05), such as pH, acidity, soluble solids, ascorbic acid, luminosity and redness of the peel and color of the pulp. Therefore, coatings made with glucomannan from Konjac may be an alternative to guarantee the quality of fruits during its commercialization, increasing its shelf life.